Weight training and plyometrics: do they affect the flying shoot of handball athletes? - Putri Cicilia Kristina; Endie Riyoko; Zihan Novita Sari (Sriwijaya Journal of Sport, 2022)
This study aims to determine: (1) the difference between weight training and plyometric training in handball athletes; (2) which exercise is better for athletes who have high motor skills who are trained with weight training or plyometric exercises on the results of flying shoots; (3) which exercise is better for athletes who have low motor skills who are trained with weight training or plyometric exercises on the results of flying shoots; and (4) whether or not there is an interaction between the training method and motor skills on the results of the flying shoot. This research is an experimental study with a 2x2 factorial design. The subjects in this study were 20 athletes at the handball club at SMAN 14 Palembang. The data analysis technique used was two-way ANOVA with a significance level of 5%. The results showed that: (1) there was a significant difference between weight training and plyometric training on the ability to flying shoot; (2) the results of flying shoots for athletes who have high motor skills who are trained with weight training are lower than the average group trained with plyometric exercises; (3) the results of flying shoots for athletes who have low motor skills who are trained with weight training are lower than the average group trained with plyometric exercises; and (4) there is a significant interaction between weight training and plyometric training on flying shoot ability.